Pelatihan Literasi Digital dan Internet Sehat bagi Perempuan di Sekolah Ibu Bahagia (SIBa) - Setiawan, Ito; Setyaningsih, Gustin; Lestari, Herwiek Diyah; Ibnu Khoer, Masyhurul Alim; Muaffak, Faisal Amar; Pribadi, Prayoga (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
SIBa was founded in June 2023. Initially, SIBa was divided into two classes. The Happy Mother School (SIBa) program aims to educate women to have a deeper understanding of their role in building a sakinah, mawaddah, warahmah family based on the principles of Ahlus Sunnah wal Jamaah. Lack of digital literacy knowledge makes it difficult for many mothers to distinguish between true and false information, which can impact child-rearing patterns and family decision-making. Strengthening digital literacy for women is an urgent need so they are able to use technology wisely, productively, and safely. With digital literacy, women can be more selective in accessing information, protecting themselves and their families from the negative impacts of cyberspace. This training activity uses a participatory approach by combining several methods of lectures, case studies, direct practice, and question and answer. The result of this training is an increase in participants' knowledge in the use of digital literacy and healthy internet to support the process of educating children and knowing the correct information on the internet.